Physiochemical and Optical Properties of GdF3:Pr@LaF3@SiO2 Microspheres - Ansari,Anees Ahmad (2018)
The polyol-based co-precipitation process was employed for synthesis of GdF3:Pr (core) and GdF3:Pr@LaF3 (core-shell) microspheres (MSs). Subsequently, an amorphous silica layer was deposited surrounding the core-shell MSs, which was verified from high-resolution transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDX) and FTIR results. The absorption spectral results revealed the high solubility with good colloidal stability in aqueous solvents. The detailed structural and morphological analysis, as well as crystallinity of the samples, was investigated through X-ray diffraction, TEM and band gap energy results. The experimentally calculated band gap energy was found to decrease after gradually coating insulating layers of LaF3 and amorphous silica over the surface, because of an effective increase in particle size. The Pr3+-doped GdF3 shows sharp 4f15d1→4f2 emission bands (260-480 nm) as well as typical 4f2→ 4f2 emission lines (460-800 nm) of Pr3+ under 4f2 →4f15d1 excitation. After surface coating, comparative photoluminescence properties of the MSs were investigated by excitation and emission spectra. The origin of the different types of emission transitions were analyzed in details.